Strong evidence for two disjunct populations of Black Scoters Melanitta americana in North America - Bowman, Timothy D.; Perry, Matthew C.; Savard, Jean-Pierre L.; Rosenberg, Daniel H.; Boyd, W. Sean; Esler, Daniel; Flint, Paul L.; Schamber, Jason L.; Gilliland, Scott G.; Osenkowski, Jason E. (Wildfowl, 2021)
Black Scoters Melanitta americana were marked with satellite transmitters on Atlantic and Pacific coasts of North America to examine continental-scale population delineation. Scoters marked on the different coasts did not overlap at any stage of the annual cycle, suggesting that birds in the two regions could be monitored and managed as separate populations: 1) an Atlantic population, which winters along the Atlantic coast and Great Lakes and breeds from northeast continental Canada westward to the Northwest Territories, and 2) a Pacific population, which winters along the Pacific coasts of Alaska, British Columbia and the Pacific northwest states, and breeds in western Alaska. Range maps for Black Scoter could reflect these distributions revealed by satellite telemetry. Our data provide new information on the distribution of Black Scoters in North America, which can be used to improve the design of future surveys.